A Concise Review of Silver Diamine Fluoride on Oral Biofilm - Jingyang Zhang; Sofiya-Roksolana Got; Iris Xiaoxue Yin; Edward Chin-Man Lo; Chun-Hung Chu (Applied Sciences, 2021)
Studies have shown that silver diamine fluoride (SDF) is an effective agent to arrest and prevent dental caries due to its mineralizing and antibacterial properties. While plenty of studies have investigated the mineralizing properties, there are few papers that have examined its antibacterial effect on oral biofilm. The objective of this study was to identify the effect of silver diamine fluoride on oral biofilm. Method: The keywords used were (silver diamine fluoride OR silver diammine fluoride OR SDF OR silver fluoride OR AgF AND biofilm OR plaque). Two reviewers screened the titles and abstracts and then retrieved the full text of the potentially eligible publications. Publications of original research investigating the effect of SDF on oral biofilm were selected for this review. Results: This review included 15 laboratory studies and six clinical studies among the 540 papers identified. The laboratory studies found that SDF could prevent bacterial adhesion to the tooth surface. SDF also inhibited the growth of cariogenic bacteria, including Streptococcus mutans, Lactobacillus acidophilus, Streptococcus sobrinus, Lactobacillus rhamnosus, Actinomyces naeslundii, and Enterococcus faecalis, thus contributing to its success in caries arrest. One clinical study reported a decrease in Streptococcus mutans and Lactobacillus sp. in arrested caries after SDF treatment, and another clinical study found that SDF inhibited the growth of periodontitis microbiota, including Porphyromonas gingivalis, Tannerella forsythia, and Prevotella intermedia/nigrescens. However, three clinical studies reported no significant change in the microbial diversity of the plaque on the tooth after SDF treatment. Moreover, one laboratory study and one clinical research study reported that SDF inhibited the growth of Candida albicans. Conclusion: Not many research studies have investigated the effects of SDF on oral biofilm, although SDF has been used as a caries-arresting agent with antibacterial properties. However, a few publications have reported that SDF prevented bacterial adhesion to the teeth, inhibited the growth of cariogenic and periodontal bacteria, and possessed antifungal properties.